PENGARUH BOKASHI PUPUK KANDANG SAPI TERHADAP PRODUKSI WORTEL (Daucus carota L.) - Wenita, Mia - (Pendidikan Biologi, 2014)
Carrot crop is a function of horticulture crops as a vegetable. Carrot market needs will continue to increase but production is still relatively low. There are several factors that influence success in the production of one of them is nurturing. Therefore research has been done in the area of allergy Long, GUMANTI Valley District, Solok regency, from December 2013 to March Month 2014. Purpose of this study was to determine the effect of cow manure fertilizer Bokashi for production of carrot (Daucus carota L.). New varieties Kuroda. In the implementation of this study was arranged in Completely Randomized Design (CRD) with five treatments and four replications. The treatments were given in a dose of fertilizer Bokashi is made up of (A) control (1.95 g Urea, TSP and KCL 3.91 g 1.46 g) / polybag, (B) 100g Bokashi fertilizer / polybag, (C) Bokashi fertilizer 140g / polybag , (D) Bokashi fertilizer 180g / polybag, and (E) Bokashi fertilizer 220g / polybag. The results showed that Bokashi cow manure with different dose of the very real influence on weight carrots, and carrots showed significant length, and has been able to increase the production of carrots.